Genetic Diversity and Population Structure of Vibrio parahaemolyticus Isolated From Clinical and Food Sources - He, Min; Lei, Tao; Jiang, Fufeng; Zhang, Jumei; Zeng, Haiyan; Wang, Juan; Chen, Moutong; Xue, Liang; Wu, Shi; Ye, Qinghua; Pang, Rui; Ding, Yu; et al. (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus is a common foodborne pathogen causing gastroenteritis worldwide. Determining the prevalence and genetic diversity of this pathogen can contribute to the minimization of the risk of infection and of the economic burden. Multilocus sequence typing (MLST) is an important tool for molecular epidemiology and population genetic studies of bacterial pathogens. In this study, we analysed the genetic and evolutionary relationships of 162 V.parahaemolyticus strains isolated in the Guangdong province, China, using MLST, a total of 120 strains were isolated from food samples, while 42 strains were isolated from clinical samples. The 162 strains were divided into 100 sequence types (STs), of which 58 were new. ST415 was the most prevalent ST in food isolates, but in clinical isolates the most prevalent one was ST3. Among these new STs, 48 (55.81%) referred to food isolates, while 10 (66.67%) referred to clinical isolates; therefore, the clinical isolates showed a higher proportion of novel STs. Moreover, there were 12 clonal complexes (CCs), 14 doublets, and 73 singletons obtained from all ST clusters, showing high genetic diversity. At the concatenated sequence level, the nonsynonymous sites of both food and clinical isolates were associated with purifying selection. Of note, in both food and clinical isolates, dN/dS >1 for some housekeeping genes. It was found for the first time that some loci were under positive selection. Our results confirmed that recombination frequently occured in V.parahaemolyticus and had a much greater effect than mutation events in the generation of genetic heterogeneity in food isolates, but the probabilities of recombination and mutations were almost equal in clinical isolates. Phylogenetic analysis showed that clinical isolates were concentrated in the maximum likelihood tree, while food isolates were heterogeneously distributed. In conclusion, this study reviewed the population and genetic diversity of food and clinical V.parahaemolyticus, using MLST. The results suggest that the food and clinical V.parahaemolyticus isolates from Guangdong province are similar, but differ in their evolutionary trends, which may help prevent the large-scale spreading of highly virulent strains and provide a genetic basis for the disclosure of the microevolutionary relationships of V.parahaemolyticus populations.